Analyze the effect of abrasives in water jet Machining on strenx steel. (2022) - Raguraman, D.; Sakthivel, P.; Paramasivam, V.; Girisha, L.; Krishnamoorthy, S.; Rahul Alex, S.; Subbiah, R.
Highlights: In present days, the demand of water jet machining (WJM) is increasing in manufacturing industries due to its excellent performance and high quality of finish. Rate of metal removal is enhancing through abrasives addition to the water. High strength and high wear resistant structural strenx 700 steel is used as the work material. Water pressure, abrasive flow and traverse speed are the control factors which used to evaluate the rate of metal removal. The combination of silicon carbide (SiC), aluminium oxide (Al2 O3 ) and garnet abrasive mixtures were used to increase the rate of metal removal. Optimization and effect of abrasive on metal removal was investigated through taguchi approach and variance analysis. Abstract: In present days, the demand of water jet machining (WJM) is increasing in manufacturing industries due to its excellent performance and high quality of finish. Rate of metal removal is enhancing through abrasives addition to the water. High strength and high wear resistant structural strenx 700 steel is used as the work material. Water pressure, abrasive flow and traverse speed are the control factors which used to evaluate the rate of metal removal. The combination of silicon carbide (SiC), aluminium oxide (Al2 O3 ) and garnet abrasive mixtures were used to increase the rate of metal removal. Optimization and effect of abrasive on metal removal was investigated through taguchi approach and variance analysis. Optimal rate of metal removal was accomplished at 300 MPa of water pressure, 50 mm/min of traverse speed and 5 g/sec of abrasive flow. The water pressure was developed the utmost effect on rate of metal removal (89.06%) than traverse speed.